Lewis acidic controllable SiO2@TiO2 core-shell for enhanced catalytic oxidation of aromatic sulfides in diesel - Yu, Zhendong; Wu, Jingyu; Li, Kaikai; Wu, Peiwen; Yu, Xiaoxiao; Tang, Minmeng; Liu, Haiyan; Liu, Zhichang; Zhu, Wenshuai; Xu, Chunming (Chemical engineering journal (Lausanne, Switzerland : 1996), 2025)
Oxidative desulfurization is an important non‑hydrogen desulfurization technology, but traditional TiO2 catalysts are subject to‌ the weak acidity and weak adsorption ability towards alkaline sulfide molecules, limited by the long reaction time for deep desulfurization. Herein, based on the principle of Lewis acid-base theory, this work reasonably designs the SiO2@TiO2 core-shell catalyst, which combines excellent catalytic oxidative desulfurization activity and product separation performance. SiO2 can regulate the acidity of TiO2 and enhance the enrichment ability of substrate molecules, enhancing the charge transfer process and improving the catalytic performance of TiO2. Through systematic characterization, it is confirmed that the Lewis acidity of the core-shell structure originates from unsaturated Ti sites. And the thickness of the TiO2 shell can be controlled to adjust the surface amounts of acid sites, strengthening the adsorption process of alkaline dibenzothiophenes. The mechanism research reveals the electron transfer between the SiO2 core and the TiO2 shell and the generated unsaturated Ti3+/Ti4+ produce a synergistic effect. The generation rates of hydroxyl radicals(·OH) and alkoxy radicals (·OR) are accelerated while changing the Lewis acidity, efficiently adsorbing and oxidizing DBTs. The work expands the application of easy-separation mild Lewis acidic TiO2 composite materials in the field of catalytic oxidation. Assembly of SiO2@TiO2 core-shell with controllable Lewis acidity for ODS. [Display omitted] •Fast oxidation of sulfides was achieved by Lewis acidic SiO2@TiO2 core-shell.•The Lewis acidity of SiO2@TiO2 core-shell was related to the thickness of TiO2.•The synergistic effect was produced by Lewis acid-base and electron transfer.•The alkaline sulfides external diffusion and oxidant activation were enhanced.